2018 National Winter Canola Variety Trial - (:unkn) unknown (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2019)
The objectives of the National Winter Canola Variety Trial (NWCVT) are to evaluate the performance of released and experimental varieties, determine where these varieties are best adapted, and increase the visibility of winter canola across the United States. Breeders, marketers, and producers use data collected from the trials to make informed variety selections. The NWCVT is planted at locations in the Great Plains, Midwest, northern U.S., and Southeast.
Keywords: canola; Kansas; Yield; Environmental Factors; National Winter Canola Variety Trial (NWCVT); oil